Corporate Governance and Tax Avoidance: A Systematic Review of Economic Implications and Influencing Factors - Putri, Ayu Fitria; Fuadah, Luk Luk; Kartasari, Shelly Febriani (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to present a systematic literature review (SLR) on the relationship between corporate governance and tax avoidance practices. Using a systematic approach, this research analyzed 45 peer-reviewed articles published between 2016 and 2024. The review focused on three primary aspects: (1) the research methodologies employed in previous studies; (2) the indicators or proxies used to measure both corporate governance and tax avoidance; and (3) the differences in findings between developed and developing countries. The findings reveal that corporate governance plays a significant role in moderating tax avoidance behavior; however, the effectiveness of governance mechanisms varies depending on institutional quality, regulatory enforcement, and ownership structures. Quantitative approaches dominate the methodological landscape, while qualitative and mixed-methods studies are emerging to explore ethical and contextual dimensions. Common governance proxies include board independence, audit committee effectiveness, and institutional ownership, while tax avoidance is primarily measured using ETR, CETR, and BTD. Studies conducted in developed countries consistently report that strong governance reduces tax avoidance, whereas in developing countries, governance effectiveness is often constrained by weak enforcement and limited market pressures. These findings provide important insights for scholars, regulators, and policymakers in strengthening adaptive governance frameworks in response to global tax challenges.